The practice and prevalence of dry sex among men and women in South Africa: a risk factor for sexually transmitted infections?. Issue 3 (1st June 1999) - Beksinska, M E; Rees, H V; Kleinschmidt, I; McIntyre, J
Abstract : OBJECTIVES: To establish the prevalence of "dry sex" practice in a South African periurban population. To investigate the reasons for and factors influencing the practice of dry sex and to evaluate dry sex practice as a risk factor for sexually transmitted disease (STD). DESIGN: Cross sectional sample survey. METHODS: A random community sample of men and women aged between 16 and 35 in Gauteng Province, South Africa, were interviewed regarding the practice of dry sex using a structured interviewer administered questionnaire. RESULTS: Dry sex practices were reported by 60% of men and 46% of women. Among younger individuals dry sex practice is far more common among the less educated, but there was no significant difference between education groups in the older respondents. A higher proportion of men practising dry sex than not practising dry sex reported having a past history of STD infection (56% versus 41%) although this difference was only marginally significant (p = 0.05). There was no difference in reported history of STD between women who practised dry sex and those who did not. CONCLUSIONS: This study shows that dry sex practice is common in this community. The younger less educated group were the most likely to practise dry sex. Dry sex practice was associated with an increased prevalence of self reported STDs in men but not in women.